2023
DOI: 10.3389/fmed.2022.1098427
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol delivery through high-flow nasal therapy: Technical issues and clinical benefits

Abstract: High-flow nasal cannula (HFNC) therapy is an oxygen delivery method particularly used in patients affected by hypoxemic respiratory failure. In comparison with the conventional “low flow” oxygen delivery systems, it showed several important clinical benefits. The possibility to nebulize drugs via HFNC represents a desirable medical practice because it allows the administration of inhaled drugs, mostly bronchodilators, without the interruption or modification of the concomitant oxygen therapy. HFNC, by itself h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Critically ill patients in the hospital are being placed on high-flow nasal cannula for the treatment of a variety of conditions that may be treated with continuous or bolus nebulization using conventional jet or mesh nebulizers. Reviews of in vitro and in vivo testing have concluded that the nasal gas flow rate must be reduced in order to mitigate aerosol losses, a maneuver with some complexity and risk [ 4 , 5 ]. It is true that aerosol losses increase with increases in high-flow rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Critically ill patients in the hospital are being placed on high-flow nasal cannula for the treatment of a variety of conditions that may be treated with continuous or bolus nebulization using conventional jet or mesh nebulizers. Reviews of in vitro and in vivo testing have concluded that the nasal gas flow rate must be reduced in order to mitigate aerosol losses, a maneuver with some complexity and risk [ 4 , 5 ]. It is true that aerosol losses increase with increases in high-flow rates.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional nebulizers can support continuous nebulization, but the range of therapy for a given concentration of drug is limited by limitations in nebulizer output (e.g., 10 mL/h). For conventional mesh nebulizers, some authors suggest that nasal flows be reduced facilitating aerosol delivery [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only nebulizers and HFNC systems allow patients to inhale aerosol with spontaneous (i.e., not forced) breathing, which makes these inhaling devices the most versatile Ingelhein Boej [ 58 , 59 ]. In other cases, i.e., when the inhalation is restricted by the external resistance of the inhaler and requires the additional inspiratory effort of a patient, the flow function Q(t) (also: PIFR and AFR —see Figure 2 ) will be different.…”
Section: The Role Of the Aerosol-generating Device And The Form Of Th...mentioning
confidence: 99%
“…The level of support can vary between invasive and non-invasive depending on the condition of the patient; it is delivered via endotracheal tube (ETT), tracheostomy tube (TT), mask, nasal cannula, or mouthpiece. High flow oxygen (HFO) therapy has become an increasingly implemented form of respiratory support as it can be used in both the hospital and homecare setting, improves patient oxygenation, reduces the work of breathing, and allows for concurrent delivery of aerosolised therapeutics for targeted treatment [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%